Cost Model Approach for Next Generation Emergency Call Systems Italy Case Study - Apak, Ahmet; Ustoglu, Ilker (SCITEPRESS, 2016)
Next generation emergency notification system after emergency call (eCall) equipped vehicle regulations with the legislation EU-2015/758 is analysed via optimal architecture selection with the study of cost modelling for the Emergency Calls EROs Handling model of European Emergency Number Association (EENA) which is applied in Italy, Austria, France, Germany and Norway. According to EU-Regulation 2015/758, public safety answering points (PSAPs) need to be ready for the new model system with the start date of 1st October 2017 while eCall-equipped vehicles are started to be produced at the end of March 2018. With this regulation, infrastructure and working procedure of eCall systems as well as eCall equipments and related vehicle structures will be updated or modified as an obligation. According to status of most appropriate 112 PSAPs, there may be an adaptation of manual eCall PSAPs, auto eCall PSAPs. In this paper, the optimal architecture of the system in Italy is discussed and the next generation crash notification systems for current Emergency Calls EROs Handling model are defined.
Keywords: Emergency Call System; 112 PSAP; Rescue Services; ERO (Emergency Response Organization); Cellular Tower Network; Crash Notification; Emergency Call Unit; eCall; PSAP; Cellular Tower; Transportation